NATIONAL EDUCATION MANAGEMENT INFORMATION SYSTEM (NEMIS) FUNDING MODELS: CHALLENGES AND WAY FORWARD (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study focused on funding models of the National Education Management Information System (NEMIS). The aim of NEMIS is to provide timely and reliable educational data that will aid policy makers and education planners make data-driven planning, decisions and policies. Data gaps occur at the three tiers of government due to challenges of NEMIS funding models. Government alone cannot bear the financial burden of EMIS, thus the need to leverage on partnering with Development Partners, Corporate Social Responsibility (CSR), PublicPrivate Partnerships (PPPs), existing funding channels. Challenges that come with these funding models include aid fragmentation, national budget deficit, high Corporate Income Taxes (CIT), informal sector tax regulations. These challenges result in setbacks at different stages of data management cycle resulting in poor education outcomes and development However, it was recommended among others that the government through sustainable nationwide security and safety that will attract domestic and foreign investors to the economy towards increased Corporate Social Responsibility to NEMIS in form of technical and financial assistance